(untitled) (mathematica didactica, 2024)
In tertiary education didactics, proof comprehension has recently established itself as a field of growing research. Although the models used there largely build upon each other, this article highlights inconsistencies in the consideration of different text levels. It merges the previous contributions into a unified model of proof comprehension. Using the example of different proof functions and different teaching goals in school and university, the connectivity and adaptivity of the unified model are demonstrated. A qualitative survey about the success criteria that students use to evaluate their proof comprehension also shows that the model is appropriate and of sufficient scope.